Seawater carbonate chemistry and photosynthetic carbon fixation rates and grazing rates of mixotrophic protists - Shai Slomka; Jolanda M H Verspagen; Jef Huisman; Susanne Wilken (PANGAEA, 2025)
We studied responses to simulated ocean acidification in three strains of the mixotrophic chrysophyte Ochromonas (CCMP1391, CCMP2951, and CCMP1393). After acclimatization of the strains to treatment with high-CO2 (1000 ppm, pH 7.9) and low-CO2 concentrations (350 ppm, pH 8.3), strains CCMP1393 and CCMP2951 both exhibited higher growth rates in response to the high-CO2 treatment. In terms of the balance between phototrophic and heterotrophic metabolism, diverse responses were observed. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Figshare (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-07-03.